2007
DOI: 10.1161/hypertensionaha.106.083592
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Utility of Pulse Pressure and Other Blood Pressure Measures for Cardiovascular Outcomes

Abstract: Abstract-Data are sparse regarding the actual predictive utility of pulse pressure and other blood pressure measures for cardiovascular events. We included all of the participants from the Chicago Heart Association Detection Project in Industry who were free of cardiovascular disease and not receiving antihypertensive treatment at baseline (1967)(1968)(1969)(1970)(1971)(1972)(1973). Baseline blood pressure measures were assessed for predictive utility for fatal and nonfatal events over 33 years. Among 36 314 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 33 publications
3
49
0
2
Order By: Relevance
“…Two large-scale, collaborative cohort studies and other recent cohort studies have reported that DBP has a strong or stronger relationship to the incidence of coronary heart disease than SBP until Bage 50; 8,11,12,32,33 thereafter, SBP and PP, but not DBP, were more influential. 8,12,[33][34][35] MAP was strongly related to the risk of coronary heart disease over a wide age range.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Two large-scale, collaborative cohort studies and other recent cohort studies have reported that DBP has a strong or stronger relationship to the incidence of coronary heart disease than SBP until Bage 50; 8,11,12,32,33 thereafter, SBP and PP, but not DBP, were more influential. 8,12,[33][34][35] MAP was strongly related to the risk of coronary heart disease over a wide age range.…”
Section: Discussionmentioning
confidence: 88%
“…[15][16][17][35][36][37][38] Recently, three large-scale collaborative cohort studies and several large-scale cohort studies have examined BP components in relation to the risk of stroke by age group. 8,[11][12][13][14] These studies have reported that the relation of DBP to stroke incidence was as strong as or stronger than that of SBP until Bage 60-65; 8,[11][12][13][14]39 thereafter, the relation of SBP to stroke incidence was stronger than that of DBP. 8,[12][13][14]35 In addition, MAP was strongly related to stroke risk over a wide age range.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 In the women of Finnmark Study, DBP was associated with incident diabetes in the age-adjusted model but not in the multivariable-adjusted model. 22 Although many studies examined PP and MAP as predictors of CVD, 23,24 there is lack of data regarding the effect of these components for prediction of diabetes, compared with other BP components. Kramer et al 21 in the Rancho Bernardo study showed that 10 mm Hg increases in PP causes a 20% increase in risk of diabetes in the multivariable-adjusted model.…”
Section: Discussionmentioning
confidence: 99%